Bortezomib is an effective enhancer for chemical probe-dependent superoxide detection - Matsumoto, Misaki; Sawada, Hikari; Iwata, Kazumi; Ibi, Masakazu; Asaoka, Nozomi; Katsuyama, Masato; Shintani-Ishida, Kaori; Ikegaya, Hiroshi; Takegami, Shigehiko; Umemura, Atsushi; Yabe-Nishimura, Chihiro (Frontiers in Medicine, 2022)
Various chemical probes for the detection of reactive oxygen species have been developed to examine oxidative stress associated with different pathologies. L-012, a luminol-based chemiluminescent probe, is widely used to detect extracellular superoxide because of its high sensitivity. We herein demonstrated that the co-application of the peptide boronic acid proteasome inhibitor, bortezomib, with L-012 significantly increased its luminescence without affecting the background. More than a five-fold increase was detected in the total luminescence of L-012 in both NADPH oxidase-expressing cells and the xanthine oxidase-dependent cell-free superoxide generation system, but not in their background. Therefore, bortezomib increased the signal-to-background ratio and improved the detection of low levels of superoxide. The application of MLN2238, another peptide boronic acid proteasome inhibitor, also enhanced the luminescence of L-012. In contrast, carfilzomib, an epoxyketone proteasome inhibitor, did not increase luminescence, suggesting that the effects of bortezomib depend on the chemical structure of the peptide boronic acid, but not on its pharmacological effects. Bortezomib-induced enhancements appeared to be specific to the detection of superoxide because the detection of H2O2 by Amplex Red/HRP was not affected by the application of bortezomib. In the quantitative detection of the superoxide-specific oxidative product 2-hydroxyethidium (2-OH-E+), the application of bortezomib resulted in a 2-fold increase in the level of 2-OH-E+. Therefore, bortezomib sensitizes the detection of superoxide in both cell-based and cell-free systems, highlighting a novel feature of compounds containing the peptide boronic acid as powerful enhancers for the detection of superoxide.